"A woman 'in the snow among the clocks and instruments'": How Adrienne Rich reimagined the lives of women astronomers. (June 2023) - Lear, Ashley; Taylor, Kayla
Abstract: The National Science Foundation's (NSF) decision to rename the Large Synoptic Survey Telescope (LSST) to the Vera C. Rubin Observatory in 2020 made it the first U.S. observatory to be named after a female astronomer. While this move fosters a heightened awareness of women's struggles for advancement in the sciences, it also indicates a need for additional historical studies of women in these fields. Our research seeks to create a new narrative for the historical experiences of women in astronomy and astrophysics through the poetry of second-wave feminist Adrienne Rich, author of Diving into the Wreck and Of Woman Born . Rich's 1968 poem "Planetarium" celebrates the career of Caroline Herschel, while also hinting at the more recent accomplishments of women astronomers like Dame Jocelyn Bell Burnell. Literary historiography is a theoretical methodology for understanding historical subjects like Herschel, through their representations in literary works. Despite the intimate format, Rich's retelling does not focus on Herschel's personal relationships but on her professional pursuits. Rich uses astronomy as a metaphor for her and other women scientists' experiences as they struggle to tune out the noise of obligations, expectations, and invisible labour, and strive to locate the signal representing individual motivation and discovery. This paper examines the professional methodologies of women in astronomy from the lens of feminist literary historiography to support science educators and policymakers in adopting gender inclusive practices. Using Rich's poem "Planetarium, " alongside the scientific processes involved in astronomical discovery, this work explores the ways in which Rich's poem reimagines astronomers like Caroline Herschel, Jocelyn Bell Burnell, and Vera Rubin, and how the piece conjures from their lives a new narrative for women in pursuit of their own vocations. The exploration of the intertwining nature of history and culture allows for an analysis of how the professional methodologies of women in astronomy relate more profoundly than differing historical periods would suggest and provides additional insight into the unique challenges currently facing women of colour in these same scientific areas. This paper seeks to contribute a new perspective in space and science communication discussions and help mitigate the dissemination of gender exclusivity in research and education. Highlights: Uses astronomy as a metaphor for women scientists' experiences. Examines professional methodologies of women in astronomy. Applies feminist historiography to the lives of women in astronomy. Attempts to mitigate the dissemination of gender exclusivity in research and education.